2006
DOI: 10.1007/s10832-006-9009-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potential and heat treatment on phase transition of alumina dielectric layer

Abstract: The characteristics and growth behaviors of alumina dielectric layer formed by anodic oxidation were investigated. The aluminum oxide layer anodized at 400 V was predominantly amorphous alumina, but at the applied potentials more than 500 V, amorphous and crystalline γ -alumina were existed in anodic oxide layer and the ratio of γ -alumina increased with the increasing applied potential. During the heat treatment at 600 • C or higher temperature, amorphous alumina layer was transformed into the crystalline γ -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Oh, H.J. et al [7] explored the structural characteristics of the surface oxide film under different voltages and found that the proportion of γ-Al2O3 in the oxide film increased with the increase of the applied voltage. The composition of the formation solution also affects the structure of the oxide film of the electrode foil.…”
Section: Study On the Optimization Of Oxide Film Propertiesmentioning
confidence: 99%
“…Oh, H.J. et al [7] explored the structural characteristics of the surface oxide film under different voltages and found that the proportion of γ-Al2O3 in the oxide film increased with the increase of the applied voltage. The composition of the formation solution also affects the structure of the oxide film of the electrode foil.…”
Section: Study On the Optimization Of Oxide Film Propertiesmentioning
confidence: 99%